Effects of Aloe Vera Compresses Patients with Fever in The GM Hospital - Pitri Ani; Lismawati; Indah Wati; Kardina Hayati; Mayang Citra Hariati (JURNAL KESMAS DAN GIZI (JKG), 2024)
Fever is one of the signs on the body that there is a process in which the body is fighting infection, the temperature of 37.5 ° C can be categorized as Fever caused by the presence of infection and autoimmune diseases, the inability of the mechanism of body heat loss can also occur due to excess production at body temperature.The World Health Organization (WHO) stated that the number of diseases in children with symptoms of fever is 62% with a mortality rate of 33%.The administration of aloevera compresses is one of the non-pharmacological interventions that can lower body temperature.The aim of this study is to find out how Aloevera Compresses affect the decrease in body temperature in fever patients. The design of this study is quasi-experimental with an approach (the one group,pretest posttest design). The sampling technique used in this study is Purposive Sampling, in which the sampler technique is based on the inclusion criteria that have been set to be respondents. The sample that was used for 3 months was 30 respondents. The results of statistical analysis using paired simple t-test obtained p value 0,000 (p<0,05) which means there is an effect of Aolevera Compress on the decrease in body temperature in fever patients. It is hoped that health workers can improve the quality of nursing staff services in improving skills in administering the effect of aloe vera compresses and can be used as information and increase knowledge.